Zanubrutinib as a salvage therapy for ibrutinib-resistant chronic lymphocytic leukemia: a case report - Lv, Zhenhui; Lu, Ping; Jing, Changhua; Yi, Xuena; Wu, Xueqiong (Frontiers in Oncology, 2025)
ObjectivesThis case report aims to evaluate the efficacy of zanubrutinib, a next-generation Bruton tyrosine kinase inhibitor (BTKi), in achieving durable disease control for patients with chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) who have experienced disease progression on ibrutinib, a first-generation BTKi.MethodsA patient with CLL/SLL who developed resistance to ibrutinib was treated with zanubrutinib. The patient’s clinical response, including disease progression, symptom control, and adverse effects, was monitored over time.ResultsThe patient demonstrated significant and durable disease control following the initiation of zanubrutinib therapy. The treatment was well-tolerated, with no severe adverse effects reported, suggesting that zanubrutinib may be an effective therapeutic option for ibrutinib-resistant CLL/SLL patients.DiscussionThe findings from this case report suggest that zanubrutinib may provide a viable treatment option for patients with CLL/SLL who have progressed on ibrutinib. Further studies and clinical trials are warranted to confirm these observations and to explore the broader applicability of zanubrutinib in managing ibrutinib-resistant CLL/SLL.